The visible nonlinear optical properties and passively Q-switched laser application of a layered PtSe2 material. Issue 2 (17th December 2019) - Cui, Na; Zhang, Feng; Zhao, Yuqing; Yao, Yongping; Wang, Qiangguo; Dong, Lulu; Zhang, Huiyun; Liu, Shande; Xu, Jinlong; Zhang, Han
Abstract : Platinum diselenide (PtSe2 ), a type-II Dirac semi-metal material, is a potential saturable absorber (SA) to generate visible pulsed lasers due to its prominent optoelectronic properties. Abstract : Platinum diselenide (PtSe2 ), a type-II Dirac semi-metal material, is a potential saturable absorber (SA) to generate visible pulsed lasers due to its prominent optoelectronic properties. A high quality PtSe2 thin film was fabricated by combining magnetron sputtering with chemical vapor deposition methods; then, its microtopography was characterized by atomic force microscopy. The saturable absorption properties and electron relaxation time in the visible region were measured via open-aperture Z -scan and femtosecond pump probe technology, respectively. The modulation depth and saturable intensity are 39.9% and 256.6 GW cm −2, respectively. The relaxation time constants were fitted to be τ 1 = (1.405 ± 0.024) ps, τ 2 = (99.03 ± 0.01) ps, and τ 3 = (2.032 ± 0.27) ns. The as-prepared PtSe2 thin film was experimentally applied as a novel SA to achieve a stable passively Q-switched (PQS) Pr:YLF visible laser. A shortest pulse width of 91.8 ns with a maximum repetition rate of 297.6 kHz was obtained. These results demonstrate that the PtSe2 thin film has promising applications in generating visible pulsed lasers.